Dwarf whale Caperea marginata Gray, 1846 of the South Atlantic - Mikhalev, Yu. A.; Budilenko, G. A. (Ukrainian Antarctic Journal, 2012)
Information about a unique form – dwarf whale Caperea marginata, from the open waters of the South Atlantic, is provided. Hydrobiological characteristics of the area is given. Size, gender and biological state of caught whales, the weight of internal organs, fullness and stomach content (Calanus tonsus, Calanus simillimus) are specified. The behavior of whales, morphological features, body proportions, and standard measurements, the structure of the baleen system, particularities of skeleton are described. Formula of the spine is determined as S<span style="background-color: #ffffff; color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">7D17L3Ca13 or S7D18L2Ca13. Allometric relationship between body length and number of vertebrae in the spine for different species of whales is established. Based on the size of females, analysis of ovaries and embryos, the average length of newborns (about 220 cm), and duration of pregnancy of females (about 11 months) are calculated. Wider habitat (using data for open water) and greater than assumed earlier populations of pygmy whales are concluded.